(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
There is an increasing interest in adding value to textiles by the use of natural products. Many of the plant materials, from which natural dyes are obtained, found to have some medicinal values. In the current study, dyeing materials were prepared from pomegranate (Punica granatum), wild mangosteen (Diospyros peregrine), myrabalan (Terminalia chebula), arjun (Terminalia arjuna), betel nut (Areca catech), onion (Allium cepa), tea (Camellia sinensis), neem (Camellia sinensis), eucalyptus (Eucalyptus cinerea) and dye flower (Coreopsis basalis). Cotton fabrics were dyed with the extracted colouring materials and were tested for their wash fastness to ensure the durability of the colour on the fabrics. Finally, the antimicrobial property of ten different natural dyed fabrics was tested against Bacillus subtilis (Gram positive) and Escherichia coli (Gram negative). The cotton fabrics dyed with extracts of arjun, betel nut, pomegranate, tea and onion were found to have antimicrobial activity against both the test bacteria at varying efficiency. The dyed fabrics also showed reasonably good wash fastness; hence have practical potential for adding antibacterial properties along with vibrant colours to textiles of medical and other delicate uses. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17327 Bangladesh J. Sci. Ind. Res. 48(3), 179-184, 2013